2019
DOI: 10.3390/f10111034
|View full text |Cite
|
Sign up to set email alerts
|

Post-Harvest Evaluation of Soil Physical Properties and Natural Regeneration Growth in Steep-Slope Terrains

Abstract: Protection of forest soils during harvesting operations is necessary to reduce damage and accelerate recovery time. The current study aims to evaluate soil physical properties, natural regeneration, and its recovery process in treatments including slope gradient, traffic intensity and skid trail after long periods of time, after ceasing the timber harvesting operations. The most recent skidding operations within each 5 years recovery period were studied for a chronosequence of 20 years. Soil samples were taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 49 publications
2
34
0
Order By: Relevance
“…Over the years after the skidding operation, the soil physical properties improve from the three-year-old trail to the 25-year-old trail, although there are significant differences with the control area. The results show that 25 years after the skidding operations, the BD, PR, and MIP were 8.4%, 27.4%, and 50.44% greater, respectively, and the TP, MP, and SM, which were 1.96%, 17.1%, and 4.58% lower than the undisturbed area, respectively. The results of this study are consistent with the results of the study by Ezzati et al [50], which reported that, 20 years after skidding operations, under high traffic intensity and gentle slope class (<20%), the bulk density was 35-42% higher and the total porosity and macroporosity were 18-24% and 19-28% lower than the undisturbed area, respectively.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Over the years after the skidding operation, the soil physical properties improve from the three-year-old trail to the 25-year-old trail, although there are significant differences with the control area. The results show that 25 years after the skidding operations, the BD, PR, and MIP were 8.4%, 27.4%, and 50.44% greater, respectively, and the TP, MP, and SM, which were 1.96%, 17.1%, and 4.58% lower than the undisturbed area, respectively. The results of this study are consistent with the results of the study by Ezzati et al [50], which reported that, 20 years after skidding operations, under high traffic intensity and gentle slope class (<20%), the bulk density was 35-42% higher and the total porosity and macroporosity were 18-24% and 19-28% lower than the undisturbed area, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…The change in the physical properties of the soil under the influence of skidding has been confirmed by other researchers, including Tavankar et al [63], Ezzati et al [50], Jourgholami at al. [32], Picchio et al [9], and Sohrabi et al [27]. The highest soil changes were obtained for high traffic intensity and slope, three years after the skidding operation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Due to the development, increase in size and weight of operating machines and their associated accessories in combination with the intensity of logging operations, especially in high humidity conditions, machine traffic in forest stands [7,[10][11][12] produces soil disturbance with drastically negative consequences. Soil disturbances caused by ground-based mechanized forest operations are usually considered as soil compaction (increase in soil bulk density) and soil displacement (lateral and longitudinal displacement of soil caused by the machine running gear), commonly referred to as rutting [7,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, soil compaction imposed by heavy machines during logging operations may dramatically affect the balancing and regulation of forest productivity process by demolishing soil structure and impairing soil physical properties [5]. Consequently, this phenomena lead to reduce the porosity in soil volume [6,7], decrease the connectivity of pore spaces [8,9], increase soil bulk density and strength [10,11], and reduce water infiltration and gas exchange [12,13], with consequent negative influences on soil macro-and micro-organisms (e.g., earthworms and microarthropods) [7,9], and elongation of root systems [14] and, ultimately, reducing tree and seedlings growth [15,16].…”
Section: Introductionmentioning
confidence: 99%